IMPLEMENTASI KURIKULUM MERDEKA SEKOLAH DASAR DI KOTA BIMA - Jumiati, Anti; Anisah, Anisah; Lastuti , Sri (Dharmas Education Journal (DE_Journal), 2024)
The independent curriculum evaluation aims to determine the extent to which the curriculum is implemented well and to identify how the Independent Curriculum is implemented in schools, learning practices and supporting factors, as well as the obstacles and challenges faced. This research uses the CIPP implementation evaluation model (Context, Input, Process, Product). Data collection methods are carried out through interviews, observation and documentation, with an approach mixed method. The interview subjects consisted of program heads, senior teachers, and students. The program head was chosen because he has strategic insight into program planning and objectives. Interview data was analyzed descriptively qualitatively, while observation data was analyzed descriptively quantitatively. The research results show that the implementation of the Merdeka Curriculum is generally considered good in all aspects of CIPP, but still needs to be improved to reach the very good criteria. The practice of implementing the curriculum is also quite satisfactory, supported by the enthusiasm of teachers and school principals in building learning communities and developing innovation. Supporting factors, such as the readiness of teaching staff and infrastructure, also play an important role in successful implementation. Barriers to research are limited textbooks, lack of teacher competence in evaluating assessments, as well as obstacles faced by students. In conclusion, the implementation of the Independent Curriculum in elementary schools throughout Bima City is considered good, but needs further improvement, especially in the aspects of assessment and provision of learning resources so that the results are more optimal.